Analisis Pengaruh Promosi, Service Quality, Brand Image Terhadap Keputusan Pelanggan Memilih Jasa Go-Jek Di Semarang - M Roby Jatmiko (Anindyaguna Ekonobisnis : Jurnal Ekonomi dan Bisnis STIE Anindyaguna, 2020)
Go-Jek is a company that serves ojek service anywhere for anyone who needs online. This research aims to know the influence of promotion, service quality and brand image on purchasing decisions of Go-Jek. Sampling method was done by using questionnaires, this study population is Go-Jek users consumer Semarang. The sample used is 84 respondents with sampling technique using purposive sampling. This study used multiple regression analysis with SPSS 21 application. The result of the research with multiple regression shows that Promotion, Service Quality, Brand Image have positive and significant effect to Go-Jek Purchase Decision. The most influential variable on Go-Jek purchasing decisions is the Brand Image.